KERJA SAMA PEMBERANTASAN PENDANAAN TERORISME DI ASIA TENGGARA - Max Fredrik Leatemia (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This paper analyzes regional cooperation on Counter Terrorism Financing (CTF) among Southeast Asian countries. Various studies have discussed the factors that construct the response of Southeast Asian countries in fighting terrorism, along with factors that undermines the counter terrorism efforts in the region. Nevertheless, these studies have not specifically adrress the risk of terrorism financing that remains high in the Southeast Asia, particularly in the frame of regional cooperation. By using the Regional Security Complex theory, this paper will explain the polarity and social structure characterizing CTF cooperation in the Southeast Asia, as well as another influential external actor. The focus of this research is on the funding aspects of dominant transnational terrorist groups after September 2001 such as Al-Qaeda and Islamic State (IS). Therefore, the discussion in this research will be focused on five countries that faced the threat of those group, i.e. Indonesia, Philippines, Malaysia, Singapore and Thailand. The findings in this article show that the characteristic of CTF cooperation in the region is largely affected by external power, while the social structure between the internal units of the region is not dominant. Thus, the efforts of the countries become ineffective in overcoming the problem of terrorism financing in the region. Keywords: Southeast Asia, Regional Cooperation, Terrorism Financing, Regional Security Complex (RSC)